The stereotypes of hosting societies about migrating populations’ education and occupational abilities, and the truth - Hà, Thị Ân (2023)
Although rarely recognized, migrants come with diverse cultural wealth, professions, skills, occupational knowledge and experiences that contribute to hosting societies. Their professions range from doctors, engineers, nurses, teachers and researchers to social workers and public service providers who were working with public and private institutions. However, their professional certificates, degrees and licenses are not easily accepted by educational institutes and labor force. The reasons that their expertise remains invisible in hosting societies often ranging from the lack of recognition of their professions by western educational institutions to requirements to upgrade their academic credits and/or accomplishments. In addition to these are the dominant stereotypes attached to refugees and immigrants from Latin America, Asia, Africa and the Middle East. As for the cultural aspect, people from the global south are already imagined as “lacking,” backward and traditional, which calls for resettled peoples to “catch up” with the modern world. Yet, most refugees are well educated and highly credentialed before they come to the U.S. This study will explore professions, skills and experiences migrants are equipped with, and examine how these abilities should be acknowledged and utilized by introducing initiatives supporting migrating populations getting back to their professions.